Peer assisted learning strategies and students with emotional/behavior disorders: a case study - Wiseman, Nicole (Kansas State University, 2018)
Students with emotional and behavioral disorders (EBD) have academic and behavioral deficits that impact their school success. For example, reading achievement of students with EBD is lower than typically developing peers and fails to improve over time without intervention. Despite this, the academic deficits of students with EBD often get overlooked and there are limited evidence-based practices for reading instruction to support them. This study sought to address this limitation by applying the Peer Assisted Learning Strategies (PALS), which has supportive evidence when applied to students with learning disabilities. The study involved eight 5th grade students, three were identified with EBD. The intervention, implemented by the classroom teacher, failed to result in gains in oral reading fluency, comprehension, and targeted social skills due to a variety of factors to be discussed. Limitations and future research are discussed, including considerations for future research.
Keywords: Peer assisted learning strategies; Emotional behavior disorders; Literacy